Studi Kasus : Asuhan Keperawatan Keluarga Dengan Diabetes Melitus - Siti Annisa Pujiwijaya; Lucia Firsty Puspita Krishna (AKPER Pasar Rebo, 2022)
Background: Diabetes Mellitus (DM) is a health problem that has a wide impact. The increasing incidence of Diabetes Mellitus and poor control of blood glucose levels can cause complications and even the risk of death. In providing family nursing care, the role of the nurse is needed to improve health status and prevent individuals and their families from complications. Objective: To provide family nursing care with Diabetes Mellitus. Method: Using a case study with a family nursing care approach to Mrs.S's family, especially Mrs.S in the Tugu Village, Cimanggis District, Depok City which was carried out on March 3 – 5 2022. Data were obtained using interviews, observation and physical examination using the approach family. Results: After a nursing assessment was carried out, a priority nursing diagnosis was established, namely unstable blood sugar levels. The interventions provided included health education on the management of Diabetes Mellitus. Conclusion: Health education provided and collaboration between the health team and Mrs.S's family can increase success in providing nursing care.